Answer:
(8 * x) + 2x = 60
8x + 2x = 60
10x = 60
/10 /10
x = 6
8 is a constant that is being multiplied by an unknown number which we will name x. It is then being added to two times the unknown number(x), so we multiply x by 2, which is 2x. The final product will be 60, so in the equation it'll then equal 60.
We consider "a number" to be a variable that withholds an unknown value, which is x (or any other variable you prefer).
Given, Customers pay $4 to enter the pumpkin patch.
And also given, customers pay $3 per pound for the pumpkins.
Given, $y be the total cost and there are x pounds of pumpkins.
The cost for pumpkin per pound = $3.
Therefore, the cost for x pound pumpkins = $(3x)
As the total cost includes the payment for entering the patch also,
So the total cost y = 3x + 4
We have got the required equation.
The equation to model the total cost is y = 3x+4.
Answer:
need points sorry 38484343
Step-by-step explanation:
Answer:
Step-by-step explanation: